Experimental Comparison of Designed Inductance Coils for Wireless Power Transfer - Shevchenko, Viktor; Khomenko, Maksym; Kondratenko, Igor; Husev, Oleksandr; Pakhaliuk, Bohdan (Electrical, Control and Communication Engineering, 2020)
The paper is devoted to the comparison of different types and different values of coils for inductive power transfer in the classical circuit. This topic is relevant with the growing demand and interest in wireless chargers and the diversity of inductance coils for wireless power transfer. The main geometric parameters affecting the coil efficiency are determined. For experimental verification the classical scheme for wireless power transfer is used based on a full-bridge inverter. Different coils at different distance between them, lateral misalignment and load resistance changed are tested. It is determined that single-layer coils have better transmit-receive efficiency than double-layer ones, especially with series-series compensation topology. The application of two-layer coils is recommended in case of high input current. The investigated samples have efficiency at the level of industrial standards. The design approach can be used for any level of power and application, including wireless charging of electric vehicle batteries.